Skn-1a/Pou2f3 specifies taste receptor cell lineage - Matsumoto, Ichiro (2011)
Functional diversification of taste cells is crucial for proper discrimination of taste qualities. We found homeodomain protein Skn-1a/Pou2f3 is expressed in sweet, umami, and bitter taste cells. The Skn-1a–deficient mice lacked electrophysiological and behavioral responses to sweet, umami, and bitter tastes, due to complete absence of sweet, umami, and bitter cells with concomitant expansion of sour cells. Skn-1a is critical for generating and balancing the diverse composition of taste cells.